Phenomenological Method in Research on Resilience of Mothers with Autistic Children in Indonesia - Aqilah, Thalsa Syahda; Ediyanto, Ediyanto; Irvan, Muchammad; Junaidi, Ahsan Romadlon (PT FORMOSA CENDEKIA GLOBAL, 2023)
Researchers often use phenomenology to study topics that are still little known or to explore sensitive content. One of them is the resilience of a mother with an autistic child. This article aims to describe the use of phenomenological research methods in studies of the resilience of mothers of children with autism. The use of literature studies is considered the most appropriate for examining how to use phenomenological studies in an effort to explore the real experiences of resilience of mothers with autistic children. By applying the 2019–2021 filtering and using the keywords phenomenological studies and resilience of mothers of autistic children, four articles were selected that met the criteria. In general, the steps in phenomenological research are bracketing, intuiting, analyzing, and describing. However, two out of the four scientific papers reviewed did not carry out bracketing and intuition. Bracketing is a characteristic of research using the phenomenological method because it limits the researcher's assumptions about the experience being studied. The process of intuiting generates a variety of data that requires exploration but does not contribute to the expansion of the experience being studied. The incompleteness of the four steps in research using the phenomenological method may result in the mixing of the resulting data with the researcher's assumptions